Dramaturgy of Ludruk Karya Budaya on the Story of Sarip Tambak Oso - Wardhani, Jihan Kusuma (Dance and Theatre Review, 2018)
This paper presents the dramaturgy of Sarip of Tambak Oso (STO), performedby Ludruk Karya Budaya Mojokerto (LKBM). LKBM as a Ludruk art group inEast Java has survived for about 47 years. The STO story has outlived the LKBMgroup. Ludruk has become a typical entertainment in East Java, and STO’s storyis one of the legends which continues to live in the people of East Java, especiallySidoarjo. STO’s story is very close to the community and the conflict in the playis a common issue in the community. This story reminds us of the importanceof good communication between the government and the community. Thisplay tells about the struggle for Sarip’ rights who does not want to pay taxesbecause of his poverty. This led to the resistance to the Dutch governmentand its accomplices. The Dutch finally found Sarip’s weakness. Sarip’s motherwould awake Sarip from death when she yelled out Sarip’s name. This storyis considered a true story by some people in the East Java region, especially inthe Oso Pond area, Sidoarjo. As the development progressed, this story laterbecame a lesson for the local community to wisely respond to all policies madeby the government. The government and the people should share the rightcommunication to create harmony. The dramaturgy study of LKBM in STO playwas important because the documentation was still relatively rare, and alsothe STO story is still contextual to date. The dramaturgy study of LKBM in theSTO play is expected to be able to become a learning, whether Ludruk as a folkart group or a story that can become known for the community.Keywords: Sarip Tambak Oso; Ludruk Karya Budaya